2002
DOI: 10.1159/000056185
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization of α<sub>2</sub>-Adrenoceptors which Regulate Noradrenaline Synthesis and Release after Chronic Treatment with Clorgyline in the Rat Brain

Abstract: The sensitivity of α2-adrenoceptors which regulate synthesis and release of noradrenaline was investigated in hippocampus, parietal cortex, and hypothalamus of rats treated with clorgyline. After administering a DOPA decarboxylase inhibitor, the in vivo tyrosine hydroxylase activity and the noradrenaline content were evaluated. Acute and chronic treatment with clorgyline led to both increases of noradrenaline levels and decreases of tyrosine hydroxylase activity, determined as the accumulation of DO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…These a 2 -ARs bind NE and decrease the release of NE from the presynaptic neurons resulting in a decrease of postsynaptic AR stimulation (Shishikina et al, 2004;Lahdesmaki et al, 2003;Roberto and Silvio, 2004;Heck and Bylund, 1998). Thus, the blockade of presynaptic a 2 -ARs with yohimbine should increase extracellular NE concentration (Galeotti et al, 2004;Prieto and Giralt, 2002). In the present study, the extracellular NE levels were already high in SPORTS rat hippocampus even in the absence of yohimbine (Figure 2a).…”
Section: Cumulative Revolution Numbers/12hrsupporting
confidence: 47%
See 1 more Smart Citation
“…These a 2 -ARs bind NE and decrease the release of NE from the presynaptic neurons resulting in a decrease of postsynaptic AR stimulation (Shishikina et al, 2004;Lahdesmaki et al, 2003;Roberto and Silvio, 2004;Heck and Bylund, 1998). Thus, the blockade of presynaptic a 2 -ARs with yohimbine should increase extracellular NE concentration (Galeotti et al, 2004;Prieto and Giralt, 2002). In the present study, the extracellular NE levels were already high in SPORTS rat hippocampus even in the absence of yohimbine (Figure 2a).…”
Section: Cumulative Revolution Numbers/12hrsupporting
confidence: 47%
“…The NE exerts its effects through its receptors (LeDoux, 1994;Cryan et al, 2004;Roberto and Silvio, 2004). Prolonged NE stimulation causes downregulation of its receptors (Prieto and Giralt, 2002). Thus, elevated extracellular NE was expected to alter the population of ARs in the hippocampus of SPORTS rats.…”
Section: Cumulative Revolution Numbers/12hrmentioning
confidence: 99%
“…The corresponding extracellular levels of 5-HIAA and DOPAC decreased to 83 and 41%, respectively. Several earlier microdialysis studies using the LCEC methods [43,[46][47][48][49] have demonstrated that MAO-A and MAO-B inhibitors cause increases in extracellular DA, NA and 5-HT levels, whereas the metabolites DOPAC and 5-HIAA were decreased. Thus, clorgyline caused significant decreases in extracellular levels of deaminated metabolites and increase in DA both after a single [50,51] or repeated [52] administration.…”
Section: Analysis Of Monoamines In Brain Extracts and Microdialysis Smentioning
confidence: 98%